Concentration and Specialisation Trends in Germany since Reunification - Jens Suedekum (Hamburg Institute of International Economics (HWWA), 2004)
In this paper we describe the development of regional specialisation and geographical concentration in Germany between 1993 and 2001. Somewhat contrary to theoretical expectations derived from the recent literature in location theory, we neither find compelling evidence for a specialisation process of German regions, nor for a concentration process of industries. By and large and with some exceptions, this conclusion holds both for West Germany and Germany as a whole, as well as for all levels of territorial aggregation (NUTS1-NUTS3). Urban areas are stronger specialised than rural districts, but also subject to faster de-specialisation. Those regions, which have increased regional specialisation against the trend, have performed significantly better in terms of employment growth.
Keywords: R12; F14; F15; 330; Regional Specialisation; Geographical Concentration; Economic Integration; Location Theory; Employment Growth; Germany; Regionale Arbeitsteilung; Regionale Konzentration; Marktintegration; Beschäftigungseffekt; Standorttheorie; Schätzung; Deutschland